Patient satisfaction after the treatment of glabellar lines with Botulinum toxin type A (Speywood Unit): a multi‐centre European observational study. (12th December 2014) - Molina, B.; Grangier, Y.; Mole, B.; Ribe, N.; Martín Diaz, L.; Prager, W.; Paliargues, F.; Kerrouche, N.
Abstract Background Whilst the efficacy and safety of glabella complex treatment with botulinum toxin type A (Speywood Unit) [BoNT‐A (s.U)] has been comprehensively studied, there are very few trials on patient‐reported outcomes and patient satisfaction associated with this treatment. Objective To assess the level of patient satisfaction 3 weeks and 4 months after the treatment of glabellar lines with BoNT‐A (s.U). Methods This is a multi‐centre, prospective, non‐interventional observational study carried out in France, Germany, Spain and the United Kingdom. Subjects were eligible if the investigator had already decided to prescribe BoNT‐A (s.U), according to the labelling. Subjects completed a questionnaire at both 3 weeks and 4 months after treatment. Results About 533 subjects completed at least one of the two questionnaires. About half of the subjects (47.9%) were naive to BoNT‐A treatment of the glabella, while 50.6% had previously received another product. A high level of satisfaction was observed after the treatment, with 94.7% and 89.6% of subjects being satisfied or very satisfied with the aesthetic outcome at week 3 and month 4, respectively. Treatment was safe and well tolerated, as directly determined in the survey. Major reasons for satisfaction included the positive aesthetic outcome, a natural appearance, a rested look and comfort of injection. Most subjects felt the treatment brought them 'harmony', 'self‐esteem/confidence' or 'youth'. Of the subjects who had previously been treated with another product, 51.2% considered the results obtained in the present study with BoNT‐A (s.U) were better. Conclusion Treatment of the glabellar lines with BoNT‐A (s.U) led to a high level of patient satisfaction and a more positive self‐perception up to 4 months after the treatment, regardless of whether the patients were naive or not to BoNT‐A treatment.